Improvement of protein production in baculovirus expression vector system by removing a total of 10 kb of nonessential fragments from Autographa californica multiple nucleopolyhedrovirus genome - Xiaoyue Zhang; Aiping He; Yuyu Zong; Houlu Tian; Zhihui Zhang; Kaixia Zhao; Xiaodong Xu; Hongying Chen (Frontiers in Microbiology, 2023)
Baculovirus expression vector system (BEVS) is a powerful and versatile platform for recombinant protein production in insect cells. As the most frequently used baculovirus, Autographa californica multiple nucleopolyhedrovirus (AcMNPV) encodes 155 open reading frames (ORFs), including a considerable number of non-essential genes for the virus replication in cell culture. Studies have shown that protein production in BEVS can be improved by removing some viral dispensable genes, and these AcMNPV vectors also offer the possibility of accommodating larger exogenous gene fragments. In this study, we, respectively, deleted 14 DNA fragments from AcMNPV genome, each of them containing at least two contiguous genes that were known nonessential for viral replication in cell culture or functionally unknown. The effects of these fragment-deletions on virus replication and exogenous protein production were examined. The results showed that 11 of the 14 fragments, containing 43 genes, were dispensable for the virus replication in cultured cells. By detecting the expression of intracellularly expressed and secreted reporter proteins, we demonstrated that nine of the fragment-deletions benefited protein production in Sf9 cells and/or in High Five cells. After combining the deletion of some dispensable fragments, we obtained two AcMNPV vectors shortened by more than 10 kb but displayed an improved capacity for recombinant protein production. The deletion strategies used in this study has the potential to further improve the BEVS.